Mode of delivery in HIV-infected pregnant women and prevention of mother-to-child transmission: changing practices in Western Europe (2010)
OBJECTIVES: To examine temporal and geographical patterns of mode of delivery in the European Collaborative Study (ECS), identify factors associated with elective caesarean section (CS) delivery in the HAART era and explore associations between mode of delivery and mother-to-child transmission (MTCT). METHODS: The ECS is a cohort study in which HIV-infected pregnant women were enrolled and their infants prospectively followed. Data on 5238 mother-child pairs (MCPs) enrolled in Western European ECS sites between 1985 and 2007 were analyzed. RESULTS: The elective CS rate increased from 16% in 1985-1993 to 67% in 1999-2001, declining to 51% by 2005-2007. In 2002-2004, 10% of infants were delivered vaginally, increasing to 34% by 2005-2007. During the HAART era, women in Belgium, UK and the Netherlands were less likely to deliver by elective CS than those in Italy and Spain (Adjusted odds ratio (AOR) 0.07 [95%CI 0.04-0.12]). The MTCT rate in 2005-2007 was 1%. Among MCPs with maternal HIV RNA <400 copies/mL (n=960), elective CS was associated with 80% decreased MTCT risk (AOR 0.20 [0.05-0.65]) adjusting for HAART and prematurity. Two infants of 559 women with viral loads <50 copies/mL were infected, one of whom was delivered by elective CS (MTCT rate 0.4% [95%CI 0.04-1.29]). CONCLUSIONS: Our findings suggest that elective CS prevents MTCT even at low maternal viral loads, but we were insufficiently powered to conclude whether this applies for levels <50 copies/ml. Diverging mode of delivery patterns in Europe reflect uncertainties regarding the risk-benefit balance of elective CS for women on successful HAART.